TiO2 Nanowire Arrays in situ Grown on Ti Foil Exhibiting Superior Uranyl-Adsorption Properties - Chen, Chun; Zhong, Yi; Liu, Xuxu; Li, Xijian; Chu, Jian; Yu, Libing; Yang, Zhenliang; Li, Bingqing; Tang, Wei; Xiong, Zhonghua; Gao, Rui (Frontiers in Materials, 2021)
TiO2 nanowire arrays in situ grown on Ti foil (TiO2/Ti) were prepared to remove uranium (VI) from aqueous solution. As the Ti foil serves as a carrier for TiO2, the TiO2/Ti adsorbent can be effortlessly retrieved from aqueous solutions by tweezers after adsorption. The presence of TiO2 nanowire arrays on Ti foil was verified by X-ray diffraction and scanning electron microscopy. Parameters in the adsorption process were fully evaluated, including solution pH, contact time, temperature, and uranium (VI) concentration. The adsorption was most efficient in the pH range of 5.0 to 9.0. The maximum uranium (VI) adsorption capacity of TiO2/Ti, based on the Langmuir model, was 354.5 mg g–1 at pH 5.0 and T = 323 K. Thermodynamic parameters showed that the adsorption of uranium (VI) on TiO2/Ti is endothermic and spontaneous. The adsorption capacity of TiO2/Ti remained essentially unchanged after three adsorption–desorption cycles in uranium (VI) solutions. Our results support the application of this adsorbent to removal of uranium (VI) from diversified aqueous samples.